The Evolution From Traditional to Online Professional Development: A Review. Issue 3 (3rd July 2017) - Elliott, Joshua C.
Abstract: Online professional development offers opportunities for growth to teachers who may not be able to participate otherwise due to constraints. These constraints include, but are not limited to, time and travel distance. This document is a narrative review of relevant literature as it relates to the evolution of teacher professional development. This evolution goes from the historical aspects of professional development through online professional development and its various modes of delivery. This discussion includes research-based perspectives of qualities found in effective professional development, specifically online professional development. Literature relating to some legislation and other guiding factors in the evolution of professional development is also discussed.